The characteristic of tinea capitis in children among dermato-venereology outpatients’ polyclinic at Sanglah General Hospital, Denpasar from 2014-2017: a preliminary study - Velava Kumar Gopal; Made Swastika Adiguna; Prima Sanjiwani Saraswati Sudarsa (DiscoverSys Inc., 2019)
Background: Tinea capitis is a type of dermatophytosis (skin disease) caused by the infection of dermatophytes. It is generally caused by the dermatophyte species of Microsporum and Trichophyton. It has been known to be able to spread human to human and animal to human. It is also almost commonly found in the prepubertal age and very rare among the adults of either gender. This study aims to determine the prevalence of Tinea capitis in children by age, sex, clinical manifestation, laboratory tests, and treatments.Methods: A cross-sectional observational study from the medical records of patients with Tinea capitis was conducted at Dermato-Venereology Outpatient Clinic RSUP Sanglah from 2014 to 2017. A total of 5 research variables were identified for this study: age, sex, clinical manifestation, laboratory tests, and treatment. The data was then analyzed and interpreted and further presented in forms of description, tables and graphs in this study by using SPSS version 17 for WindowsResults: A total of 32 patients were identified as having Tinea capitis from the period of 2014–2017. There was a slightly higher prevalence in the male gender (56.25%) compared with female gender (43.75%). The highest prevalence of the disease was found in the age groups of 1 – 5 and 6 – 10 years old with 43.75% respectively. Majority of the patients showed the presence of grey patch on their scalp on examination (53.13%). The dermatophyte Trichophyton rubrum had the highest isolation in comparison with other dermatophytes at 25.00%. The patients were almost all treated with oral Griseofulvin.Conclusion: The majority diagnosis of Tinea capitis was found in group 1-5 and 6-10 years old and had a grey patch appearance, whereas Trichophyton rubrum as the highest isolation in comparison with other dermatophytes